Improving The Quality of Service to Students at Ibnu Sina University - Cundara, Nandar; Herman; Prakasa Hasibuan, Rizki (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research data was conducted to determine the quality of teaching and learning process services currently available and to improve the quality of Teaching and Learning Process services at Ibnu Sina University by distributing questionnaires to Ibnu Sina University students totaling 267 respondents. The research variables created in the questionnaire refer to 5 dimensions of service, namely Tangible, Reliability, Responsiveness, Assurance, Emphaty. From the measurement results using the Servqual method, from all dimensions of service quality, students still feel dissatisfied because the gap value is still negative (-) and the negative value is the highest among the 5 The service quality dimension is the tangible dimension with the highest gap value of -0.98, followed by the responsiveness dimension with a value of -0.81. From the results of the quadrants produced using the Cartesian diagram, quadrant 1 is the main priority in improving service quality.